The Chronology of Augustine’s "Tractatus in Iohannis Evangelium" 1–16 and "Enarrationes in Psalmos" 119–133 Revisited - Andokova, Marcela; Horka, Robert (Vox Patrum, 2019)
In the year 2002 Milewski published an article devoted to the current state of research concerning Augustine’s Commentary on the Gospel of John where, among other topics, he reports on the state of research in the chronology of this work by Augustine, and after a brief summary of the latest solutions proposed by prominent Augustinian scholars he concludes that the history of the Tractates’ composition calls for a careful appreciation of their development and appearance over the course of Augustine’s busy episcopate and in relation to his other pastoral endeavours. This study therefore serves as the point of departure for our present article in which we would like to contribute to the recently proposed solution to certain questions related to the chronology of the two series of Augustine’s homilies, i.e. Tractatus in Iohannis Evangelium 1-16 and Enarrationes in Psalmos 119-133, especially in those points where the present solutions appear to be rather vague. Hence, our analysis concerns primarily the division of Tractates 1-12 and 13-16 made by Le Landais, and consequently accepted by all later scholars. Moreover, it focuses on some key points of the chronology: the dating of Tractate 7 at a pagan festival, the so-called dies sanguinis, proposed by La Bonnardière, then the synchronization of Tractates 1-16 with the parallel series of Enarrationes in Psalmos 119-133, and, finally, the re-evaluation of the year of the delivery of both series of homilies, dated between the years 406/407 or 407/408. Our argumentation is based, first and foremost, on the principle similar topic means similar liturgical time thanks to which we can place Tractates 10-12 of the Commentary on John’s Gospel right before the beginning of the Lenten season. Consequently, it enables us to include Tractates 13-16 in Augustine’s preaching activity during the Lenten season until as late as the beginning of the Easter Octave. In addition, if we admit that Tractate 7 was not delivered on the so-called dies sanguinis feast related to the rites of Cybele and Attis but on the occassion of another unknown local festival of an aitiological myth in Hippo Regius, we do not need to place it on the 24th of March as La Bonnardière did. Finally, these findings help us outline the new synchronized chronology of the two series of Augustine’s exegetical homilies for both the years 406/407 and 407/408.